Effective Mine Ventilation Management without Compromising Mine Health & Safety and Productivity - W. E. Oching; M. M. Ghomshei (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
"Collaboration among Ventilation Engineers, Mine Inspectors, worker representatives, health and safety officers and management is key to an effective operational mine ventilation management. Mine ventilation training, ventilation survey reports for mine stakeholders and interaction with mine frontline workers and management concerning safety, energy saving, assets management and maintenance are effective tools in implementing best industry practices and significant reduction of ventilation operating costs without compromising safety. These approaches may not be new to well established mining companies but the real dilemma is how to implement them effectively and this is what this paper will address.INTRODUCTIONManaging an effective mine ventilation system is becoming increasingly challenging, especially during tough economic times in the mining industry. Management strives for more production while frontline miners work hard to surpass the production targets, thus improving their incentives and above all aiming to enhance the prospects of their job security when the mining industry is facing challenging times. Taking shortcuts by not fully following the safety regulations or industry best practices are often notable, resulting in the rise of Workers Compensation Board claims and temporary shutdowns of active workings, compromising productivity and increasing the operating costs.In accordance with the Mines regulations in various jurisdictions in Canada and the US, it is evident that companies adhere to establishing basic ventilation management systems through the provision of the code of practice, procedures, work practices and standards/guidelines. This is aimed at ensuring the health and safety of underground workers (de Souza, 2017). However, the challenge to many operations is the improper implementation of the mine ventilation regulations including some managers showing reckless disregard for workers safety by focusing on production and not worrying to address ventilation problems (Steven & O'Keefe, 2010). Other challenges facing effective ventilation management include inadequate training of frontline workers on ventilation system and hazards associated with poor ventilation systems such as toxic gases, dust, heat, and underground explosions (Mufson et al., 2010; Suvar et al., 2017); friction between mine managers and the mine inspectors (Mufson et al., 2010), improper maintenance of ventilation system and inventory management, among others."